Paul Valéry e Anne Carson em torno do que não existe - Helena Martins (O Que Nos Faz Pensar)
This essay presents a reading of Paul Valéry’s “Short Letter on Myths” alongside Anne Carson’s “Visibles Invisibles” – an unusual juxtaposition that also tests a Carsonian critical method. Imagining Carson’s text as a response to Valéry’s letter, it aims to construe the dialog between the two authors as a form of misrouted correspondence, centered on the interplay between art, illusion and truth. More specifically, it shows how this imagined exchange displaces and intensifies a vital paradox addressed in Valéry’s letter, namely that of the presence of what does not exist. The essay starts from the perception that the dystopian life we lead today is marked by a rarefaction of this vital paradox, the relevance of reflecting on it lying therein.